Implementation of Moratorium by Islamic Banks During the Covid-19 Pandemic: Maqasid Shariah Perspective - Mohamed Othman, Nurul Balqis; Rosman, Romzie (2021)
The Covid-19 pandemic has caused unprecedented health and economic crisis. The significant measures adopted by most countries to contain the virus by implementing movement control order (MCO) led to an economic downturn. The decision to implement the lockdown follows the rising number of Covid-19 cases in the country where 8,290 new Covid-19 cases reported on 28th May 2021. The lockdown will definitely cause hardship for the economic wellbeing of the people. Hence, this paper examines the central bank policy implication on the practice of moratorium after the first MCO on 18th March 2020 to support the people and company that badly affected by the lockdown for them to pay their loan and financing. The paper highlight the issue and challenges in the implementation of moratorium by Islamic banks. Furthermore, the study will provide policy implications and importantly to support the value-based intermediation for Islamic banks to fulfil the Maqasid Shariah.